Análise biomecânica de dente tratado endodonticamente com comprometimento estrutural - efeito do procedimento restaurador - Valdivia, Andréa Dolores Correia Miranda (2011)
Unresolved controversy exists concerning the the most appropriate technique used to restore endodontic treated teeth. The purpose of this study was to evaluate the effect of four types of restorations associated or not with glass fiber post after thermal cycling on the strain, fracture resistance, and fracture mode of endodontically treated human incisors. Ninety human maxillary central incisors with similar dimensions were selected and distributed in 9 groups (n=10), one control group (IT) and 8 treatment groups Rc- composite resin without fiber post; Dcv- direct composite veneer without fiber post; Cvfeldspathic ceramic veneer without fiber post; Cc- feldspathic ceramic crown without fiber post; RcGfp- composite resin with fiber post; DcvGfp- direct composite veneer with fiber post; CvGfp- feldspathic ceramic veneer with fiber post; CcGfp- feldspathic ceramic crown with fiber post. The teeth were endodontic treated and received two large class III preparation simulating coronal destruction, then were restored without glass fiber post or with glass fiber post (Gfp) and four restorative techniques: direct composite resin (Rc), direct composite veneer (Dcv), feldspathic ceramic veneer (Cv) and feldspathic ceramic crown (Cc). Following artificial aging by thermal cycling, the buccal and proximal strain were measured by strain-gauges attached on external dentin, under load of 100 N at 0.5 mm/min applied with inclination of 135° to the long axis of the tooth. Specimens were subsequently loaded to the point of fracture. Strain and fracture resistance results were analyzed by one-way and two-way ANOVA (4x2), followed by the Tukey HSD tests (α=.05). One-way analysis showed significant difference (P=.000). among all groups with respect to fracture resistance values, test showed that intact teeth and teeth restored with composite resin, irrespective of post presence, presented significant higher resistance to fracture. Two-way analyses showed no significant differences for system post (P=.959). Proximal strain values were higher in control and composite resin groups; and lower in feldspathic ceramic groups. The presence of glass fiber post did not increase fracture resistance of endodontically treated incisors. Conservative composite resin restoration presented higher fracture resistance values.